Region 1 New England LEGISLATIVE Update The Tobacco Institute April 3 1987 Washington DC NATIONAL TOPICS (Tufts Archival Research Center, 2007)
Legislative update for New England. Discusses activities occuring in each state and the strategy of the industry with regard to each issue. Contains an alert blog which lists all the bills currently being debated as well as people to watch out for or to thank.